EMPLOYMENT AND WOMEN'S ENTREPRENEURSHIP - Ibodullayeva M.S. (Web of Journals Publishing, 2025)
This article highlights the differences between the terms business and entrepreneurship, as well as the problems encountered by women's entrepreneurship in the current market economy, and also touches on the achievements that can be achieved by attracting women to business. The level of women's employment in our country and in the Samarkand region is also analyzed.
Keywords: Women's employment, women's business, unemployment, business, entrepreneurship, women's employment, women's business, women's notebook.